Etika Profesi Dewan Pengawas Syariah - Syai'in, Syai'in (IAIN Kudus, 2018)
Among distinction between conventional banking and Islamic banking is the organizational structure. At Islamic banking and other islamic financial institutions should have a sharia supervisory board. The Shari'ah supervisory board is located in the central office and its function is to oversee the business activities of the bank in accordance with the principles of shari'ah. In carrying out its functions, the Shari'a supervisory board must follow the DSN fatwa. In the early days, members of the DPS banking were only proposed by the bank institution to DSN-MUI to obtain a decree as a ligality of their membership. Therefore at that time the syari'ah bank to propose candidates for the Shari'ah supervisory board simply chose someone who became a religious leader, cleric and ulama in the place of work of the bank.After issuing the DSN-MUI Decree No. 02 of 2000, DPS membership is made an extension of the DSN whose legality is improved in the membership mechanism through competency testing, which is in the DSN Language to attend